Design and Synthesis of Novel Nordihydroguaiaretic Acid (NDGA) Analogues as Potential FGFR1 Kinase Inhibitors With Anti-Gastric Activity and Chemosensitizing Effect - Chen, Qian; Zhu, Min; Xie, Jingwen; Dong, Zhaojun; Khushafah, Fatehi; Yun, Di; Fu, Weitao; Wang, Ledan; Wei, Tao; Liu, Zhiguo; Qiu, Peihong; Wu, Jianzhang; et al. (Frontiers in Pharmacology, 2020)
Aberrant fibroblast growth factor receptor-1 (FGFR1), a key driver promoting gastric cancer (GC) progression and chemo-resistance, has been increasingly recognized as a potential therapeutic target in GC. Hereon, we designed and synthesized a series of asymmetric analogues using Af23 and NDGA as lead compounds by retaining the basic structural framework (bisaryl-1,4-dien-3-one) and the unilateral active functional groups (3,4-dihydroxyl). Thereinto, Y14 showed considerable inhibitory activity against FGFR1. Its anti-gastric activity is superior to that of lead compounds, which may be due to the increased lipophilicity of Y14 and hydrophobic interactions as the dominant force in the binding of FGFR1 to Y14. Furthermore, we confirmed that Y14 showed anti-gastric activity and chemosensitizing effect by inhibiting the phosphorylation of FGFR1 in vitro. These results indicate that Y14 is an effective FGFR1 inhibitor and is expected to become a potential candidate for the treatment of GC either alone or in combination with chemotherapy.